Evaluating Art Therapy to Heal the Effects of Trauma Among Refugee Youth: The Burma Art Therapy Program Evaluation. Issue 1 (January 2017) - Rowe, Cassandra; Watson-Ormond, Rose; English, Lacey; Rubesin, Hillary; Marshall, Ashley; Linton, Kristin; Amolegbe, Andrew; Agnew-Brune, Christine; Eng, Eugenia
Background . Art therapy uses the creative process to encourage personal growth and alleviate symptoms of mental illness. The Art Therapy Institute provides programs for refugee adolescents from Burma to decrease their trauma-related symptoms. This article describes and discusses the methods and findings from an evaluation of this program. The challenges of assessing art therapy with this population and assessment tool gaps are explored and suggestions for future evaluations discussed. Method . Four validated clinical assessment tools were administered to 30 participants at baseline and follow-up to measure symptoms of anxiety, depression, and behavioral problems. Focus group discussions with clinicians were used to assess the evaluation. Results . Nearly all participants had experienced one or more traumatic events. At baseline, results showed a higher prevalence of depression than national rates among adolescents. Follow-up results showed improvements in anxiety and self-concept. Qualitative findings suggest that specific benefits of art therapy were not adequately captured with the tools used. Discussion . This evaluation showed some effects of art therapy; however, symptom-focused assessment tools are not adequate to capture clients' growth resulting from the traumatic experience and this unique intervention. Future evaluations will benefit by using an art-based assessment and measuring posttraumatic growth.